Electrophopretic variation in feral populations of three freshwater species of fish - Doyungan, Zaldy F.; Mencias, Claire D.; Isidro, Stephanie P.; Rosales, Ma. Theresa U. (1998)
Analysis of hemoglobin and plasma esterase in the blood sample of three feral freshwater species of fish, namely, spotted gourami (Trichogaster trichoptenus)
Keywords: Mindanao studies